2019
DOI: 10.36298/gerais2019120213
|View full text |Cite
|
Sign up to set email alerts
|

Adulto autor de violência sexual: estudo exploratório de avaliação de risco de reincidência

Abstract: _____________________________________________________________________________________ ResumoO presente texto trata de uma pesquisa qualitativa realizada no contexto de um programa de atendimento psicossocial grupal ao autor adulto de violência sexual. O objeto está centrado no estudo exploratório da avaliação de risco de reincidência do ato violento por meio da aplicação de um instrumento atuarial complementar ao instrumento da entrevista. O método de pesquisa foi a análise documental. O instrumento SVR-2.0 é … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
3
0
6
Order By: Relevance
“…Relating to this data, the study by Carvalho and Nobre (2013) found a higher number of schemas related to the domain of impaired autonomy and performance in sexual offenders of children and adolescents than in the group of non-offenders. The vulnerability to harm schema may be directly related to the experiences in the family of origin of these individuals, since many reported the occurrence of substance abuse by the father, in addition to experiences of victimization, both physical, sexual and psychological, common in families with substance abuse (Reichenheim et al, 2012;Carvalho, & Nobre, 2013;Ferreira, 2020;Fonseca, Setubal, & Costa, 2019). In addition, Finkelhor (1984), as well as Howitt (2009), discuss the emotional fragility of the victimizer related to immaturity, need for domination/control, narcissism and the stage of development of the child and/or adolescent, which ultimately justifies the childish emotional needs of the victimizers, which are provided in relations with children and/or adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Relating to this data, the study by Carvalho and Nobre (2013) found a higher number of schemas related to the domain of impaired autonomy and performance in sexual offenders of children and adolescents than in the group of non-offenders. The vulnerability to harm schema may be directly related to the experiences in the family of origin of these individuals, since many reported the occurrence of substance abuse by the father, in addition to experiences of victimization, both physical, sexual and psychological, common in families with substance abuse (Reichenheim et al, 2012;Carvalho, & Nobre, 2013;Ferreira, 2020;Fonseca, Setubal, & Costa, 2019). In addition, Finkelhor (1984), as well as Howitt (2009), discuss the emotional fragility of the victimizer related to immaturity, need for domination/control, narcissism and the stage of development of the child and/or adolescent, which ultimately justifies the childish emotional needs of the victimizers, which are provided in relations with children and/or adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…A falta de indicadores oficiais sobre esse público de autores de violência sexual marca tanto a falta de conhecimento quanto a dificuldade de se estudar o fenômeno no Brasil (Fonseca, Setubal, & Costa, 2019;Wolff, Oliveira, Marra, & Costa, 2016). Assim, observa-se que as informações sobre as características do autor de violência sexual ficam restritas ao contexto da área de saúde, devido ao esforço de pesquisadores e estudiosos do tema, concentradas principalmente nas regiões Centro-Oeste (Fonseca et al, 2019;Penso et al, 2016;Wolff et al, 2016), Sul e Sudeste (Baltieri & Boer, 2015;Valença, Meyer, Freire, Mendlowicz, & Nardi, 2015).…”
Section: A Ofensa Sexual De Crianças E/ou Adolescentesunclassified
“…A falta de indicadores oficiais sobre esse público de autores de violência sexual marca tanto a falta de conhecimento quanto a dificuldade de se estudar o fenômeno no Brasil (Fonseca, Setubal, & Costa, 2019;Wolff, Oliveira, Marra, & Costa, 2016). Assim, observa-se que as informações sobre as características do autor de violência sexual ficam restritas ao contexto da área de saúde, devido ao esforço de pesquisadores e estudiosos do tema, concentradas principalmente nas regiões Centro-Oeste (Fonseca et al, 2019;Penso et al, 2016;Wolff et al, 2016), Sul e Sudeste (Baltieri & Boer, 2015;Valença, Meyer, Freire, Mendlowicz, & Nardi, 2015). O Boletim Epidemiológico da Secretaria de Vigilância em Saúde (2018) aponta que os ofensores sexuais de crianças e/ou adolescentes são majoritariamente homens e eles possuem vínculo familiar com a vítima, sendo pais, padrastos, avôs, entre outros, assim como apontam Penso et al (2016) e Schaefer, Brunnet, Lobo, Carvalho, e Kristensen (2018).…”
Section: A Ofensa Sexual De Crianças E/ou Adolescentesunclassified
“…(2018) e Fonseca, Setubal e Costa(2019) complementam que, em todos os casos, o agressor exerce de alguma forma poder sobre a vítima através de ameaças, chantagem ou intimidação, sendo assim, Coutinho e Morais (2018) destacam a importância do grupo familiar, da rede informal e das redes de apoio institucionais como principal suporte para a vítima decidir revelar o abuso.…”
unclassified